One child : life, love and parenthood in modern China - Fong, Mei (2016)
POPULATION & DEMOGRAPHY. For over three decades, China exercised unprecedented control over the reproductive habits of its billion citizens. Now, with its economy faltering just as it seemed poised to become the largest in the world, the Chinese government has brought an end to its one-child policy. It may once have seemed a shortcut to riches, but it has had a profound effect on society in modern China. Combining personal portraits of families affected by the policy with a nuanced account of China's descent towards economic and societal turmoil, Pulitzer Prize-winning journalist Mei Fong reveals the true cost of this most controversial of policies. Drawing on eight years spent documenting its repercussions, she reveals a dystopian legacy of second children refused documentation by the state, only children supporting their parents and grandparents, and villages filled with ineligible bachelors.